Proportion and characteristics of men with unknown risk category in the National Prostate Cancer Register of Sweden. (1st December 2016) - Tomic, Katarina; Westerberg, Marcus; Robinson, David; Garmo, Hans; Stattin, Pär
Abstract: Background: Knowledge on missing data in a clinical cancer register is important to assess the validity of research results. For analysis of prostate cancer (Pca), risk category, a composite variable based on serum levels of prostate specific antigen (PSA), stage, and Gleason score, is crucial for treatment decisions and a strong determinant of outcome. The aim of this study was to assess the proportion and characteristics of men in the National Prostate Cancer Register (NPCR) of Sweden with unknown risk category. Material and methods: Men diagnosed with Pca between 1998 and 2012 registered in NPCR with known or unknown risk category were compared with respect to age, socioeconomic factors, comorbidity, cancer characteristics, cancer treatment, and mortality from Pca and other causes. Results: In total, 3315 of 129 391 (3%) men had unknown risk category. Compared to other men in NPCR, these men more often had a concomitant bladder cancer diagnosis, 19% versus 1%, diagnosis of benign prostatic hyperplasia 31% versus 5%, received unspecified Pca treatment 16% versus 3%, had higher comorbidity, Charlson Comorbidity Index 2 or higher, 34% versus 13%, and had lower Pca mortality 12% versus 30%, but similar mortality from other causes. Conclusion: Men with unknown risk category were rare in NPCR but distinctly different from other men in NPCR in many aspects including higher comorbidity and lower Pca mortality.